Analisis Pengaruh Promosi, Saluran Distribusi, Orang, Proses, dan Bukti Fisik Terhadap Keputusan Nasabah Menabung Di Tabungan Simpeda Pada PT. Bank Kalbar Cabang Mempawah - Lastri 01 (Universitas Muhammadiyah Pontianak, 2014)
This study aimed to analyze the effect of promotion, place, people, processes, and physical evidence against the decision of customers save money in the Savings Simpeda at PT. Mempawah Branch Bank of West Kalimantan. This study used a survey method, which obtained the data from interviews, questionnaires, and corporate documents. The population in this study is the whole number of customers Savings Simpeda at PT. Bank Branch Mempawah West Kalimantan last year that amounted to 21 327 people. While the samples of 100 were selected by the provisions have become customers Savings Simpeda based purposive sampling. The analysis tool used is linear. From the results of hypothesis testing simultaneous effect (F test) showed that promotion, place, people, process and physical evidence simultaneously significantly influence consumer decisions to save. Hypothesis test showed that the promotion is partially significant effect on consumer decisions in Savings Simpeda save on PT. West Kalimantan Regional Development Bank Branch Mempawah.